Interactions of the choroid, Bruch's membrane, retinal pigment epithelium, and neurosensory retina collaborate to form the outer blood-retinal-barrier. (May 2020) - Fields, Mark A.; Del Priore, Lucian V.; Adelman, Ron A.; Rizzolo, Lawrence J.
Abstract: The three interacting components of the outer blood-retinal barrier are the retinal pigment epithelium (RPE), choriocapillaris, and Bruch's membrane, the extracellular matrix that lies between them. Although previously reviewed independently, this review integrates these components into a more wholistic view of the barrier and discusses reconstitution models to explore the interactions among them. After updating our understanding of each component's contribution to barrier function, we discuss recent efforts to examine how the components interact. Recent studies demonstrate that claudin-19 regulates multiple aspects of RPE's barrier function and identifies a barrier function whereby mutations of claudin-19 affect retinal development. Co-culture approaches to reconstitute components of the outer blood-retinal barrier are beginning to reveal two-way interactions between the RPE and choriocapillaris. These interactions affect barrier function and the composition of the intervening Bruch's membrane. Normal or disease models of Bruch's membrane, reconstituted with healthy or diseased RPE, demonstrate adverse effects of diseased matrix on RPE metabolism. A stumbling block for reconstitution studies is the substrates typically used to culture cells are inadequate substitutes for Bruch's membrane. Together with human stem cells, the alternative substrates that have been designed offer an opportunity to engineer second-generation culture models of the outer blood-retinal barrier.